Review: 3D printing hydrogels for the fabrication of soilless cultivation substrates. (September 2021) - Kalossaka, Livia M.; Sena, Giovanni; Barter, Laura M.C.; Myant, Connor
Highlights: Hydrogels could be used as substitutes for soilless cultivation substrates. A fabrication system that prints multiscale structures still needs to be developed. Structures integrating hydrogels with photosynthetic organisms have been fabricated. Graphical abstract: Abstract: The use of hydrogels in academic research is fast evolving, and becoming more relevant to real life applications across varying fields. Additive Manufacturing (AM) has paved the way towards manufacturing hydrogel substrates with tailored properties which allow for new functionalities and applications. In this review, we introduce the idea of fabricating hydrogels as bioreceptive structures to be used as soilless cultivation substrates. AM is suggested as the fabrication process to achieve structures with features similar to soil. To evaluate this, we first review hydrogel fabrication processes, highlighting their key differences in terms of resolution, printing speed and build volume. Thus, we illustrate the examples from the literature where hydrogels were 3D printed with microorganisms such as algae. Finally, the challenges and future perspectives of printing soilless cultivation substrates are explored.